Analysis of expert assessments of the central Asia-China summit in the context of Kazakhstan's cooperation with the SCO countries (Journal of Philosophy Culture and Political Science, 2023)
Cooperation with China is an important aspect of the foreign policy of the Central Asian countries and a research topic that is of great interest among representatives of the scientific community. This article is devoted to the analysis of expert assessments obtained following the results of the Central Asia-China summit. Summits, top-level meetings between various countries and regions, play an important role in shaping world politics and the economy. They provide participants with an opportunity to discuss issues related to security, trade, cooperation and many other aspects of international relations. The Central Asia-China Summit is no exception.Central Asia remains a strategically significant region that attracts the attention of many world powers. In turn, China, with its huge economic potential and geopolitical role, is playing an increasingly important role in this region. Thus, expert assessments about the summit can provide valuable information about the current state and future of cooperation.The purpose of the study: To identify the strengths and weaknesses, opportunities and threats of the decisions taken at the Central Asia-China summit, held on May 18-19, 2023 in Xi'an, based on expert assessments and to reveal its impact on the further development of cooperation between the parties.Each category is grouped into four criterias: foreign policy, economy, new areas of cooperation and security.The results are interpolated in such a way as to determine how strengths can be enhanced by opening opportunities, how strengths can be used to minimize the consequences of possible threats, how to level weaknesses with an emphasis on prospects, and what measures should be taken to prevent the escalation of weaknesses by potential threats.Key words: China, Central Asia, SWOT analysis, risks, prospects, assessment.